Role of isoflavones and its derivatives on the growth of Aspergillus niger and Rhizactonia solani - V, Daniel; D, Krupadanam (Journal of Phytology, 2012)
Two naturally occurring isoflavones genistine and biochanin - A, and their dihydro derivatives (isoflavones) as well as nine perhydroginated isoflavones (isoflavanes) were tested for their effects on mycelial growth of two soil fungi viz., Aspergillus niger and Rhizactonia solani. All the isoflavonenoids of the biochanin - A series showed the genistine isoflavane and the other isoflavanes with two hydroxyl groups and one methoxy groupe are fungi toxic, while isoflavones with two and one methoxy group were almost inactive.